Owning the genome : a moral analysis of DNA patenting - Resnik, David B. (State University of New York Press, 2004)
"DNA patenting has emerged as a hot topic in science policy and bioethics as private companies and government agencies spend billions of dollars on genetic research and development in a race to identify, sequence, and analyze DNA from human, animal, and plant species. David B. Resnik's Owning the Genome explores the ethical, social, philosophical, theological, and policy issues surrounding DNA patenting and develops a comprehensive approach to the topic. Resnik considers arguments for and against DNA patenting and concludes that only a patent on a whole human genome would be inherently immoral, while the morality of other DNA patents depends on their consequences for science, medicine, agriculture, industry, and society. He also stresses the importance of government regulations and policies in order to minimize the harmful effects of patenting while promoting the beneficial ones."